Self-assembled monomolecular layer material and application thereof

By introducing intramolecular conformational lock structures or fused ring structures into self-assembled single-layer materials, the problem of insufficient density and stability of materials is solved, and the material film formation properties and carrier transport capacity are improved, and the efficiency and stability of optoelectronic devices are significantly improved.

CN119912426APending Publication Date: 2025-05-02SHENZHEN UNIVERSITY OF ADVANCED TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411905989.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing self-assembled single-layer materials have shortcomings in terms of density and stability, and are susceptible to external factors such as humidity, temperature and chemical reagents, and insufficient interaction force between molecules, resulting in low overall stability and functionality of the material.

Method used

The self-assembled single-layer material of the functional backbone is introduced with heteroatom-containing conjugated structures with intramolecular conformational locking structures or fused ring structures to enhance the π-π interaction and coplanarity between molecules, thereby improving the film formation and stability of the material.

Benefits of technology

By introducing intramolecular conformational lock structure or fused ring structure, the density and stability of self-assembled single-layer materials are significantly improved, and the carrier transport capacity of the material and the efficiency and stability of the optoelectronic devices are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912426A_ABST
    Figure CN119912426A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy materials, in particular to a self-assembled monomolecular layer material and application thereof. A conjugated unit with an intramolecular conformation lock or condensed ring structure is introduced into a self-assembled monomolecular layer material with a functional framework, so that the intermolecular acting force and coplanarity are improved, the film-forming property of the material is improved, and the overall compactness and stability are enhanced. When the compound is used as a hole transport layer material or used for hole transport layer modification, the efficiency and stability of a photoelectric device can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a self-assembled monolayer material and application thereof. Background Art

[0002] Self-assembled monolayers (SAMs) are a technology that forms highly ordered monolayers on the surface of a substrate by spontaneously arranging molecules. This technology relies on the precise arrangement of organic molecules on a suitable substrate. These molecules usually have specific functional groups and can form a monolayer on the surface of the substrate through chemical bonds and weak intermolecular interactions. Due to its strong structural designability, controllable thickness and excellent surface functionalization capabilities, self-assembled monolayers have become an important object of research on functional surface materials.

[0003] A typical self-assembled monolayer material consists of three parts: first, a functional skeleton that enables efficient carrier extraction, responsible for providing the required physical and chemical properties; second, a linking group that gives the molecule the necessary freedom to adapt to the substrate surface; and finally, an anchoring group that can form a strong covalent bond with a substrate such as conductive glass. Through the synergistic effect of these three parts, self-assembled monolayer materials can achieve precise control of surface properties at the molecular level, efficiently match with specific electrode materials, and optimize charge injection and transfer efficiency.

[0004] However, the existing preparation process of self-assembled monolayers is easily affected by external factors such as humidity, temperature and chemical reagents, and the intermolecular interaction force of self-assembled monolayers is insufficient, resulting in insufficient molecular arrangement and insufficient density of the formed monolayer, thereby reducing the overall stability and functionality of the material. In addition, the molecules of self-assembled monolayer materials are mainly connected by van der Waals forces, and the binding force with the substrate is relatively weak. It is easy to desorb or change its structure under long-term environmental exposure or mechanical stress, which significantly limits its application in scenarios with high stability requirements.

[0005] In summary, existing self-assembled monolayer materials have obvious deficiencies in density and stability and are in urgent need of further improvement. Summary of the invention

[0006] The present invention introduces a heteroatom-containing conjugated structure having an intramolecular conformation lock structure or a condensed ring structure into a self-assembled monolayer material having a functional skeleton, thereby providing a self-assembled monolayer material and application thereof.

[0007] Specifically, the present invention provides the following technical solutions:

[0008] The first aspect of the present invention provides a self-assembled monolayer material, comprising a functional skeleton, a connecting group and an anchoring group, wherein the connecting group connects the functional skeleton and the anchoring group, and the connecting group comprises an intramolecular conformational lock structure and / or a condensed ring structure.

[0009] Preferably, the intramolecular conformation lock structure comprises substituted or unsubstituted Figure 1 Any one or more of the structural formulas shown; wherein X is any one of O, S, Se, and Te; Y is any one of F, Cl, O, S, and C; R is any one of a saturated or unsaturated cyclic, linear, or branched carbon chain structure; d1 is the distance between the X atom and the Y atom, which is less than the sum of the van der Waals radii of the X atom and the Y atom.

[0010] Preferably, the torsion angle between the five-membered rings where the X atom is located, or between the five-membered ring where the X atom is located and the benzene ring where the Y atom is located is θ1, and the range thereof is 0°≤θ1≤90°.

[0011] Preferably, the intramolecular conformation lock structure comprises substituted or unsubstituted Figure 2 The structural formula shown in FIG. 1 ; wherein X is any one of O, S, Se, and Te; Y is any one of F, Cl, O, S, and C; Z is an H atom; R is any one of a saturated or unsaturated cyclic, linear, or branched carbon chain structure; and d2 is the distance between the Z atom and the Y atom, which is less than the sum of the van der Waals radii of the Z atom and the Y atom.

[0012] Preferably, the torsion angle between the five-membered ring where the X atom is located and the benzene ring where the Y atom is located is θ2, and the range thereof is 90°≤θ2≤180°.

[0013] Preferably, in the above substituted structural formula, the position of the substituent is the ortho and / or meta position of the X atom; the substituent is any one or more of H, F, Cl, Br, I, CN, NH2, OH, C1-C20 alkyl, and C1-C20 alkoxy.

[0014] In the above intramolecular conformation lock structure, the distances d1 and d2, and the torsion angles θ1 and θ2 are mathematical parameters that describe the coplanarity of the molecular structure. Specifically, the distances d1 and d2 are the key to prove the core interactions between related elements to form the conformation lock, and the torsion angles θ1 and θ2 further characterize the coplanarity of the molecular conformation.

[0015] Preferably, the condensed ring structure comprises Figure 3 Any one or more of the structural formulas shown; wherein X1 is any one of S, Se, and Te; and X2 is any one of H, S, Se, Te, and N.

[0016] Preferably, the functional skeleton comprises substituted or unsubstituted Figure 4 Any one or more of the fluorene derivatives, carbazole derivatives, triphenylamine derivatives, diphenylamine derivatives, acridine derivatives, phenothiazine derivatives, phenoxazine derivatives, anthracene derivatives, anthraquinone derivatives, xanthanone derivatives, perylene derivatives, naphthalene diimide derivatives, perylene diimide derivatives, tetraphenylethylene derivatives, triphenylethylene derivatives, coronene derivatives, triphenylborane derivatives, triphenylphosphine derivatives, perylene derivatives, benzophenone derivatives, and triphenylene derivatives; in the substituted fluorene derivatives, carbazole derivatives, acridine derivatives, xanthanone derivatives, benzophenone derivatives, and phenothiazine derivatives, the position of the substituent is the 4th position and / or the 9th position; in the substituted triphenylamine derivatives and diphenylamine derivatives, the position of the substituent is opposite to the N atom.

[0017] Preferably, the linking group is directly connected to the functional skeleton through a covalent bond or connected through a covalent bond spacer atom; the linking group is directly connected to the anchoring group through a covalent bond or connected through a covalent bond spacer atom; the spacer atom is any one or more of a carbon atom, an oxygen atom, a nitrogen atom, and a sulfur atom.

[0018] Preferably, the anchoring group includes any one or more of a hydroxyl group, a carboxyl group, a phosphate group, a thiol group, an amino group, a sulfonic acid group, and a boric acid group.

[0019] The second aspect of the present invention provides an application of a self-assembled monolayer material in the preparation of an optoelectronic device, wherein the optoelectronic device uses the self-assembled monolayer material as a hole transport layer, or uses the self-assembled monolayer material to perform interface modification on the hole transport layer.

[0020] The beneficial effects of the present invention are:

[0021] (1) The self-assembled monolayer material provided by the present invention is composed of a functional skeleton, a linking group and an anchoring group, wherein the linking group is designed to have a conjugated structure with an intramolecular conformation lock structure or a condensed ring structure. The heteroatoms in the conjugated structure can interact with the intermolecular carbon-hydrogen bonds, improve molecular conjugation, enhance the π-π interaction in molecular stacking, enhance the intermolecular force and coplanarity, thereby improving the film-forming property of the material and enhancing the overall compactness and stability.

[0022] (2) The self-assembled monolayer material provided by the present invention has high density and stability. The anchoring groups therein can produce strong interactions with the perovskite or metal oxide substrate. When the material is used as a hole transport layer material or for hole transport layer modification, the high density can enhance the carrier transport capacity of the device, and the anchoring groups can passivate the perovskite defects, thereby improving the efficiency and stability of the optoelectronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a structural formula of a heteroatom-containing conjugated structure having a conformational lock in one embodiment;

[0024] Figure 2 is a structural formula of a heteroatom-containing conjugated structure having a conformational lock in one embodiment;

[0025] Figure 3 is a structural formula of a conjugated structure containing heteroatoms and having a condensed ring in one embodiment;

[0026] Figure 4 is a molecular structural formula of a functional main skeleton in one embodiment;

[0027] Figure 5 is the molecular structure formula of the self-assembled monolayer material, wherein A is the functional skeleton, B is the connecting group, and C is the anchoring group;

[0028] Figure 6 is a synthetic reaction formula of the self-assembled monolayer material BY-1 in one embodiment;

[0029] Figure 7 is a synthetic reaction formula of the self-assembled monolayer material BY-2 in one embodiment;

[0030] Figure 8 is a schematic diagram of the structure of a perovskite solar cell in an embodiment;

[0031] Fig. 9 is a current density-voltage curve diagram of a perovskite solar cell in an embodiment;

[0032] Fig.10 is a diagram showing the stability of the photoelectric conversion efficiency of a perovskite solar cell in an embodiment;

[0033] Fig.11 Schematic diagram of the structure of a perovskite solar cell in one embodiment. DETAILED DESCRIPTION

[0034] The technical solution of this patent will be further described in detail below in conjunction with specific implementation methods. It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by ordinary technicians in the technical field to which this application belongs.

[0035] like Figure 5As shown, the present invention provides a self-assembled monolayer material, which includes a functional skeleton A (circle), a connecting group B (rectangle) and an anchoring group C (arrow), wherein the connecting group is a heteroatom-containing conjugated structure with an intramolecular conformational lock structure or a condensed ring structure, and the anchoring group can interact with a perovskite or metal oxide substrate.

[0036] Example 1: Synthesis and characterization of self-assembled monolayer material BY-1

[0037] (1) Figure 6 As shown, compound 1, compound 2, Pd(PPh3)4 and potassium carbonate are placed in a dry Schlenk reaction bottle, and the dosage is 1eq, 1eq, 0.05eq and 2.5eq, respectively. Nitrogen is introduced into the reaction bottle after evacuation, and repeated three times to ensure an inert atmosphere. Subsequently, a mixed solvent of tetrahydrofuran and water in a volume ratio of 7:1 is added, and the mixture is placed in an 80°C oil bath and stirred for 3h until the reaction reaches equilibrium. After the reaction is cooled to room temperature, the palladium catalyst is removed by silica gel chromatography, the reaction solution is washed with water, and extracted with ethyl acetate to obtain a yellow solid crude product, which is directly used in the next step without purification.

[0038] (2) The crude product was dissolved in a mixture of tetrahydrofuran and methanol in a volume ratio of 5:1, 10 eq of potassium hydroxide was added, and the mixture was stirred at 75°C for 12 h. After the reaction, the mixture was acidified to weak acidity with a 1M hydrochloric acid solution, extracted with dichloromethane, and the organic phase was collected and the solvent was removed by rotary evaporation. The mixture was then separated and purified by silica gel column chromatography and finally dried in vacuum to obtain the self-assembled monolayer material BY-1.

[0039] Results: The self-assembled monolayer material BY-1 is an orange-red solid with a chemical formula of C 31 H 25 NO4S, the yield is 72%. BY-1 molecules are easy to crystallize, the crystal belongs to the triclinic system, the space group is α=85.211°(2),β=76.945°(2),γ=70.398°(2), the unit cell volume is

[0040] Product BY-1 1 The H NMR spectrum signal is: 1H NMR (400MHz, Chloroform-d, δ (ppm)): δ8.15-8.09 (m, 2H), 7.72 (d, J = 8.4Hz, 2H), 7.49-7.39 (m, 3H), 7.21(d,J=3.8Hz,1H),7.11(d,J=8.8Hz,4H),6.95(d,J=8.4Hz,2H),6.92-6.82(m,4H),3.83(s,6H).

[0041] Example 2: Synthesis and characterization of self-assembled monolayer material BY-2

[0042] like Figure 7 As shown, the synthesis steps of the self-assembled monolayer material BY-2 are basically the same as those of BY-1, except that compound 3 and compound 4 are used as reactants.

[0043] Results: The self-assembled monolayer material BY-2 is an orange-red solid with a mass of 116 mg and a yield of 63%. BY-2 has an intramolecular conformation lock structure, its molecules cannot crystallize, and its own film-forming property is strong, and it is easy to evenly coat and form a dense film.

[0044] Product BY-2 1 The H NMR spectrum signal is: 1 H NMR (400MHz, Chloroform-d, δ (ppm)): δ7.8 (d, J = 4.2Hz, 1H), 7.8-7.7 (m, 1H), 7.2 (d, J = 4.0Hz, 1H), 7.0 (dd, J = 11.8, 8.8Hz, 4H), 6.8 (dd, J=14.7, 9.0Hz, 4H), 6.7 (dd, J=12.6, 7.0Hz, 1H), 4.4 (d, J=12.8Hz, 4H), 3.8 (s, 5H), 3.7 (s, 1H).

[0045] Example 3: Application of self-assembled monolayer materials BY-1 and BY-2

[0046] Dissolve the self-assembled monolayer materials BY-1 and BY-2 in ethanol to prepare a precursor solution with a concentration of 0.5-1 mg / mL. Take 50-100 μL of the precursor solution and evenly spin-coat it on a surface area of ​​2.25-6 cm 2 The spin coating speed was set to 3000 rpm and the spin coating time was 30 s. After the spin coating, the sample was annealed at 100 °C for 10 min to form a hole transport layer on the indium tin oxide glass substrate. Figure 8The structure shown is used to prepare a perovskite solar cell, which includes, from bottom to top, a substrate, a transparent oxide electrode, a hole transport layer, a photoactive layer, an electron transport layer, a hole blocking layer and a metal electrode.

[0047] result: Fig. 9 The current density-voltage curve of the perovskite solar cell is shown, and Table 1 shows the photovoltaic data of perovskite solar cell devices based on different self-assembled monolayer materials.

[0048] Table 1 Photovoltaic data of perovskite solar cell devices based on different SAMs

[0049]

[0050] It can be seen that the photoelectric conversion efficiency of perovskite solar cells using BY-1 and BY-2 as hole transport layers reached 25.09% and 26.04%, respectively, which are significantly higher than those of the control group using MeO-2PACz and Me-4PACz, indicating that BY-1 and BY-2 materials have stronger capabilities in promoting the conversion of light energy into electrical energy.

[0051] In addition, the open circuit voltage of the perovskite cells based on the self-assembled monolayer materials BY-1 and BY-2 is significantly higher than that of the MeO-2PACz and Me-4PACz control groups, indicating that BY-1 and BY-2 materials can effectively reduce voltage loss, thereby improving the overall efficiency of the cell. At the same time, the short-circuit current density of the BY-1 and BY-2 groups is greater, showing a higher ability to generate photocurrent and enhancing the output power of the cell. At the same time, the increase in fill factor further proves that perovskite cells based on BY-1 and BY-2 can achieve higher power output.

[0052] Fig.10 The results of the maximum power point operation stability test of perovskite solar cells with different material groups under a solar simulator are shown. It can be seen that after 500 hours of continuous illumination, the photoelectric conversion efficiency of perovskite solar cells based on MeO-2PACz and Me-4PACz significantly decayed, while the perovskite cells based on BY-1 and BY-2 remained stable without obvious decay. This shows that BY-1 and BY-2 have better light stability than traditional MeO-2PACz and Me-4PACz materials.

[0053] What needs to be understood is:

[0054] First, the above embodiments take BY-1 and BY-2 as examples to introduce the structure and synthesis method of the self-assembled monolayer material, but the technical solution provided by the present invention has wide applicability. Figure 1 or Figure 2 Any one or more of the structural formulas shown as intramolecular conformational lock structures, or Figure 3 Any one or more of the structural formulas shown in the figure can be used as a condensed ring structure to form a connecting group based on an intramolecular conformational lock structure and / or a condensed ring structure, thereby synthesizing a self-assembled monolayer material, improving the film-forming property of the material, and enhancing the overall compactness and stability; substituted or unsubstituted Figure 4 Any one or more of the structural formulas shown are used as functional skeletons; any one or more of hydroxyl, carboxyl, phosphate, thiol, amino, sulfonic acid, and boric acid groups are used as anchoring groups; different connection methods are used to connect the connecting group and the anchoring group, and the connecting group and the functional skeleton into one, thereby synthesizing a self-assembled monolayer material and improving the efficiency and stability of the optoelectronic device obtained based on the material. These should not be limitations on the present application.

[0055] Secondly, the above embodiment takes perovskite solar cells as an example to introduce the application of self-assembled monolayer materials in optoelectronic devices. In practical applications, the self-assembled monolayer materials provided by the present application can also be used in other optoelectronic device structures, such as organic solar cells, quantum dot solar cells and other single-junction thin-film solar cells; organic / perovskite stacked solar cells, all-perovskite stacked solar cells, perovskite / crystalline silicon stacked solar cells and other stacked solar cells; or perovskite light-emitting diodes, etc., which should not be a limitation to the present application.

[0056] Third, the above embodiments take the self-assembled monolayer material as the hole transport layer material in the solar cell as an example to introduce the application of the self-assembled monolayer material in the optoelectronic device. In practical applications, the self-assembled monolayer material provided by the present application can also be used for interface modification on the basis of the original hole transport layer. This should not be a limitation to the present application.

[0057] Fourthly, the above embodiment takes the structure of substrate / transparent oxide electrode / hole transport layer / photoactive layer / electron transport layer / hole blocking layer / metal electrode as an example to introduce the application of self-assembled monolayer materials in optoelectronic devices. In practical applications, it can also be used for Fig.11 Among the other battery structures shown: 1) substrate / SAM / perovskite / electron transport layer / electrode; 2) substrate / electron transport layer / perovskite / SAM / electrode; 3) substrate / SAM / organic light absorbing layer / electron transport layer / electrode; 4) substrate / electron transport layer / organic light absorbing layer / SAM / electrode; 5) substrate / hole transport layer / SAM / perovskite / electron transport layer / electrode; 6) substrate / hole transport layer / SAM / organic light absorbing layer / electron transport layer / electrode, this should not be a limitation to the present application.

[0058] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A self-assembled monolayer material, characterized in that: It comprises a functional skeleton, a connecting group and an anchoring group, wherein the connecting group connects the functional skeleton and the anchoring group, and the connecting group comprises an intramolecular conformation lock structure and / or a condensed ring structure.

2. The self-assembled monolayer material according to claim 1, characterized in that: The intramolecular conformation lock structure includes any one or more of the following substituted or unsubstituted structural formulas: Wherein, X is any one of O, S, Se, and Te; Y is any one of F, Cl, O, S, and C; R is any one of a saturated or unsaturated cyclic, linear or branched carbon chain structure; d1 is the distance between the X atom and the Y atom, which is smaller than the sum of the van der Waals radii of the X atom and the Y atom.

3. The self-assembled monolayer material according to claim 2, characterized in that: The torsion angle between the five-membered rings where the X atom is located, or between the five-membered ring where the X atom is located and the benzene ring where the Y atom is located, is θ1, and its range is 0°≤θ1≤90°.

4. The self-assembled monolayer material according to claim 1, characterized in that: The intramolecular conformation lock structure includes the following substituted or unsubstituted structural formula: Wherein, X is any one of O, S, Se, and Te; Y is any one of F, Cl, O, S, and C; Z is a H atom; R is any one of a saturated or unsaturated cyclic, linear or branched carbon chain structure; d2 is the distance between the Z atom and the Y atom, which is smaller than the sum of the van der Waals radii of the Z atom and the Y atom.

5. The self-assembled monolayer material according to claim 4, characterized in that: The torsion angle between the five-membered ring where the X atom is located and the benzene ring where the Y atom is located is θ2, and its range is 90°≤θ2≤180°.

6. The self-assembled monolayer material according to any one of claims 2 to 5, characterized in that: In the substituted structural formula, the position of the substituent is the ortho and / or meta position of the X atom; the substituent is H, F, Cl, Br, I, CN, NH2, OH, C1-C20 alkyl 、 Any one or more of C1-C20 alkoxy groups.

7. The self-assembled monolayer material according to any one of claims 1 to 5, characterized in that: The condensed ring structure includes any one or more of the following structural formulas: Wherein, X1 is any one of S, Se, and Te; X2 is any one of H, S, Se, Te, and N.

8. The self-assembled monolayer material according to claim 7, characterized in that: The functional skeleton includes any one or more of substituted or unsubstituted fluorene derivatives, carbazole derivatives, triphenylamine derivatives, diphenylamine derivatives, acridine derivatives, phenothiazine derivatives, phenoxazine derivatives, anthracene derivatives, anthraquinone derivatives, xanthanone derivatives, perylene derivatives, naphthalene diimide derivatives, perylene diimide derivatives, tetraphenylethylene derivatives, triphenylethylene derivatives, coronene derivatives, triphenylborane derivatives, triphenylphosphine derivatives, perylene derivatives, benzophenone derivatives, and triphenylene derivatives; In the substituted fluorene derivatives, carbazole derivatives, acridine derivatives, xanthenone derivatives, benzophenone derivatives, and phenothiazine derivatives, the position of the substituent is 4-position and / or 9-position; In the substituted triphenylamine derivatives and diphenylamine derivatives, the substituent is located at the para position to the N atom.

9. The self-assembled monolayer material according to claim 8, characterized in that: The linking group is directly connected to the functional skeleton through a covalent bond or connected through a covalent bond spacer atom; the linking group is directly connected to the anchoring group through a covalent bond or connected through a covalent bond spacer atom; the spacer atom is any one or more of a carbon atom, an oxygen atom, a nitrogen atom, and a sulfur atom.

10. The self-assembled monolayer material according to claim 8, characterized in that: The anchoring group includes any one or more of a hydroxyl group, a carboxyl group, a phosphate group, a thiol group, an amino group, a sulfonic acid group, and a boric acid group.

11. Application of a self-assembled monolayer material in the preparation of optoelectronic devices, characterized in that: The photoelectric device uses the self-assembled monolayer material of any one of claims 1 to 10 as a hole transport layer, or uses the self-assembled monolayer material of any one of claims 1 to 10 to perform interface modification on the hole transport layer.